ANALISIS KAPASITAS AEROBIK DAN ANAEROBIK PENDAYUNG ROWING MENGGUNAKAN WATTBIKE DAN ERGOMETER ROWING CONCEPT II - Alfy Fauzia Azmi, - (2022)
The purpose of this study was to find out "whether there are differences in aerobic and anaerobic capacities using the Wattbike and Rowing Ergometer Concept II". The research method used is the ex-post facto method with purposive sampling technique, namely 6 rowing athletes in the city of Bandung, with the criteria for determining the sample are rowing athletes with rowing numbers with male gender. The research instrument used was a wattbike test and an ergometer test, then this finding was in accordance with the assumptions formulated, namely that there were differences in the results of aerobic and anaerobic tests using a wattbike and ergometer rowing concept II. shows the results of the paired samples t-Test test between the aerobic wattbike and the ergometer rowing concept II with a t-value of 0.429 and a sig.(2-tailed) value of 0.689. Then the anaerobic wattbike and ergometer concept II are known to have a t value of 13,336 and a Sig. (2-tailed) value of 0.000 which is greater than 0.005. it can be concluded that there are differences in aerobic and anaerobic capacities using a wattbike and ergometer rowing concept II.